Knowledge, Attitude and Practices of Oral Health among Parents and Pre-School Children - Suriani Binti Ismail, Mohammed Khalid Salim Alsharif, Ahmad Iqmer Nashriq Mohd Nazan, (Opción, 2019)
The aim of the study is to investigate the knowledge, attitude and practices of oral health among parents and pre-school children via comparative qualitative research methods. As a result, there is significantly correlation between frequency of tooth brushing in parents and frequency of tooth brushing in their children. Children learn many of their habit and skill from their parents. In conclusion, knowledge, attitude and practice of patents are the most important characteristic factors that have influence on oral hygiene of their preschool children.